2015
DOI: 10.1038/nature14883
|View full text |Cite
|
Sign up to set email alerts
|

Structural integration in hypoxia-inducible factors

Abstract: The hypoxia-inducible factors (HIFs) coordinate cellular adaptations to low oxygen stress by regulating transcriptional programs in erythropoiesis, angiogenesis and metabolism. These programs promote the growth and progression of many tumours, making HIFs attractive anticancer targets. Transcriptionally active HIFs consist of HIF-α and ARNT (also called HIF-1β) subunits. Here we describe crystal structures for each of mouse HIF-2α-ARNT and HIF-1α-ARNT heterodimers in states that include bound small molecules a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
357
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(379 citation statements)
references
References 64 publications
21
357
0
1
Order By: Relevance
“…Although AHR and ARNT have similar domain structures (Fig. 1A), we observed that ARNT curls around the AHR into a highly intertwined asymmetric architecture, similar to those of the CLOCK-BMAL1 and the HIF-α-ARNT complexes (33,34). The bHLH and PAS-A domains of AHR and ARNT form extensive domain-domain and cross-domain interactions via highly conserved residues of AHR ( Fig.…”
Section: Quaternary Architecture Of Ahr-arnt Heterodimer Inmentioning
confidence: 89%
See 1 more Smart Citation
“…Although AHR and ARNT have similar domain structures (Fig. 1A), we observed that ARNT curls around the AHR into a highly intertwined asymmetric architecture, similar to those of the CLOCK-BMAL1 and the HIF-α-ARNT complexes (33,34). The bHLH and PAS-A domains of AHR and ARNT form extensive domain-domain and cross-domain interactions via highly conserved residues of AHR ( Fig.…”
Section: Quaternary Architecture Of Ahr-arnt Heterodimer Inmentioning
confidence: 89%
“…1C). Although not visible in the structure, several loops of AHR and ARNT PAS-A domains bear positively charged residues, which could be oriented for interaction with the target DNA outside the DRE consensus sequence (34) (Fig. S3C).…”
Section: Specific Recognition Of Dre and Comparison With Hypoxia Respmentioning
confidence: 99%
“…2A). The significance of these perturbations became apparent in light of a recently published crystal structure of the more complete HLH-A-B heterodimer of HIF2a and ARNT, which revealed an alternative spatial arrangement and interface of the two PAS-B domains (25). Although the folds for both HIF2a PAS-B domain structures are essentially identical, the domain arrangement of the HLH-A-B dimer revealed that the PT2385 perturbed amino acids are now located at the HIF2a/ARNT PAS-B interface (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of the recently reported crystal structure of the more complete helix-loop-helix:PAS-A:PAS-B (HLH-A-B) heterodimer of HIF2a and ARNT reveals that the HIF2a/ARNT PAS-B Ã domains occupy a completely different spatial arrangement and dimer interface (25). In this orientation, the perturbed residues now reside at the HIF2a/ARNT PAS-B interface, suggesting that PT2385-induced changes to residues H293, M252, and Y278 are responsible for dimer disruption (Fig.…”
Section: Binding and Dimerization Disruptionmentioning
confidence: 99%
“…There are no known endogenous ligands for HIF-2α, but this cavity has been targeted for drug development and several promising highly specific smallmolecule inhibitors have been identified that efficaciously disrupt HIF-2α heterodimerization with ARNT and block DNA binding and transcription of target genes in cultured cells (141). These reagents coupled with recent HIF structural analysis provide a framework to specifically regulate HIF-1α and HIF-2α and will aid the development of clinical tools to alter protumor inflammatory responses or antitumor immune responses (142).…”
Section: Hif-based Therapeutics In Cancermentioning
confidence: 99%